2000
DOI: 10.1055/s-2000-13215
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Microvascular Responses to Sepsis

Abstract: The liver is believed to play a major role in the initiation of multiorgan failure, the most lethal complication in the clinical course of sepsis. Microbes and their virulence factors enter the hepatic circulation where they first activate sinusoidal endothelial cells and Kupffer cells to produce proinflammatory mediators, including TNF-alpha, IL-1, IL-6, reactive oxygen metabolites, and eicosanoids. These mediators cause not only microbial killing, but also structural and functional liver damage concerning ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 42 publications
3
29
2
Order By: Relevance
“…Liver injury and dysfunction are typical features of the multiple organ failure complicating clinical gram-negative septic shock (27). The data presented here support a possible role of flagellin as an initiator of such abnormalities.…”
Section: Discussionsupporting
confidence: 70%
“…Liver injury and dysfunction are typical features of the multiple organ failure complicating clinical gram-negative septic shock (27). The data presented here support a possible role of flagellin as an initiator of such abnormalities.…”
Section: Discussionsupporting
confidence: 70%
“…39 Therefore, a breakdown of liver tolerance and the resulting inappropriate or excessive immune responses in the liver should be considered to be the main reason for bacterial infections that are related to acute and chronic inflammatory liver diseases. 40 This explains the phenomena whereby liver injury and dysfunction are common in patients with severe sepsis and septic shock, 41 where a large number of bacterial-derived TLR agonists are produced. The current study suggested that flagellin is an important initiator of liver injury in severe bacterial infections because flagellin circulates in significant concentrations in the plasma of patients with typhoid fever 42 or septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of LPS as a potent inducer of hepatic innate immune responses and liver injury during severe bacterial infection is widely established, 41 the pathological role of flagellin in the liver remains elusive. By creating deletion variants of recombinant flagellin, FliCD1-180 and FliCD90-97 derived from Salmonella typhi, we confirmed that deleting amino acids 1-180 or 90-97 of flagellin substantially abolished the TLR5 activity of flagellin, and diminished the proinflammatory cytokine response and subsequent acute liver function abnormality and damage.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,9,15 Because septic shock and sequential multiple organ failure are strongly correlated with poor outcome and high mortality, 3 establishing the factors affecting prognosis, and implementing new diagnostic and management strategies are important. Sepsis is defined as a systemic inflammatory response (SIRS) to infectious factors, and severe sepsis is defined as "sepsis associated with multiorgan failure, hypoperfusion abnormality, or sepsis-induced hypotension."…”
Section: Discussionmentioning
confidence: 99%